Strengthening Youth Ecological Engagement Through Mobile Learning: An Experimental Study with Eco-Facilitator Coaching - Wongsonadi, Sri Kuswantono; Hikmah; Lestari, Retno Dwi; Parinduri, Fitri Khoiriyah (International Journal of Science and Society, 2025)
Rapid environmental degradation in urban areas has intensified the demand for educational strategies that can foster sustained ecological engagement among marginalized youth. This study evaluates the effectiveness of a hybrid intervention integrating a mobile learning application, JawaraEco, with eco-facilitator coaching in enhancing multidimensional ecological engagement. An experimental design was implemented, involving 232 urban youth from four densely populated subdistricts in Jakarta, randomly assigned to either an experimental group (receiving access to the app and coaching) or a control group (no intervention). Data were collected through in-app behavioral metrics and a validated ecological engagement scale, encompassing cognitive, emotional, behavioral, and continuity dimensions. Statistical analyses, including paired and independent samples t-tests as well as two-way ANOVA, revealed significantly greater gains across all dimensions in the experimental group. These findings demonstrate that combining mobile learning with structured human facilitation fosters more robust and sustained ecological behaviors. The study contributes practical insights for scalable implementation in schools, community programs, and local governance, while also offering theoretical support for technology-supported, socially embedded environmental learning ecosystems.